Kegiatan Keislaman di SMA Muhammadiyah 3 Surakarta dan Pengaruhnya Terhadap Pembentukan Karakter Anak - Arifkha, Desiyana Nurul; , Dr. Ari Anshori, M.Ag (2017)
Islamic activities are religious activities. Where in this activity there are programs that in trying to create and build a religious attitude of children. This Islamic ctivity is also a religious vessel that moves independently where the container is managed and developed by the child and the facilitator of the activity, so that structurally and onally it can be said as an institution that has stewardship. The objectives to be achieved in this activity are can provide support for character formation of children. The problem studied in this research is how Islamic activity in SMA Muhammadiyah 3 Surakarta and its influence to character formation of child. The purpose of this study is to find out Islamic activities in SMA Muhammadiyah 3 Surakarta and its influence on the character formation of children. The cation of research in SMA Muhammadiyah 3 Surakarta and the subject of research is Islamic activity in SMA Muhammadiyah 3 akarta and its influence on the character forming of children. This research is a field research using qualitative research type. The method used in this research is interview, rvation and documentation. Data analysis method used in this research is inductive method. Based on the analysis of data obtained, it can be concluded that the Islamic activities in SMA Muhammadiyah 3 Surakarta is seven minutes speech, dhuha prayer, reading al-Qur'an before starting lesson, practicing infaq every friday and IMMA (Intensity of Reading Write al-Qur'an). And for the influence of this Islamic activities on the formation of children's character is that before they follow the activities of Islam in school, they are only limited to know what is the cult, pray dhuha, reading al-Qur'an, infaq and IMMA, as after they follow their Islamic activities not only know but also can practice it in everyday life. For other influences that is easy to understand students learning PAI, children are more orderly in implementing prayers fardhu or sunnah prayer in school, the level of ability of children in learning the better, children become more generous, morals children become better, children can read and write al-Qur'an, children are more responsible for everything they do and children can care about each other. Keywords: Islamic Activities, Character, Children.